The effect of young blood plasma administration on gut microbiota in middle-aged rats - Ceylani, Taha; Teker, Hikmet Taner (Springer, 2022)
Numerous in-depth studies continue to reveal the many benefits of gut microbiota and young blood plasma administration. Dysbiosis, which occurs in the intestinal microbiota, especially in the aging process, is associated with many metabolic and cognitive disorders. Therefore, many studies aim to reverse the dysbiosis that occurs. There are also studies showing that young blood plasma application reverses the effects of aging at the level of many tissues and organs. Today, while research continues to reveal all the benefits of young blood plasma application in terms of health, blood plasma centers are also being established. In this study, we aimed to reveal the impact of young blood plasma, administered for 1 month, on the intestinal microbiota of middle-aged rats. After detailed metagenome analysis, alpha diversity indices demonstrated greater bacterial richness in the microbiota of plasma-administered rats compared with control rats. In addition, the Firmicutes/Bacteroidetes ratio was significantly diminished in plasma group microbiota, confirming possible rejuvenation properties of young plasma. Furthermore, increased counts of Bifidobacterium longum, Coprococcus catus, and Romboutsia ilealis species were measured in plasma-administered rats. The study revealed many fluctuations in different bacterial taxonomic units of the microbiota that could be valuable in future research on blood-based anti-aging treatments.
Keywords: Young blood plasma; Gut microbiota; Metagenome; Alpha diversity; Middle-aged rat; Cells; Rejuvenation; Mice